2014
DOI: 10.1097/qai.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

HIV Communication Capacity Strengthening

Abstract: HIV communication is most effective and sustainable when it is designed and implemented locally and tailored to the local context. This requires capacity strengthening at national, subnational, and community levels. Through a review of the published and selected "grey" literature, we examine HIV communication capacity strengthening: definitions, measurements, implementation, and effects. We found limited documentation of HIV communication capacity needs or systematic approaches to address them. Most HIV commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The demand for better interpersonal quality of care may reflect that women experience brusque and disrespectful treatment by providers in resource-constrained health systems [40, 41]. The need for effective communication and more empathetic treatment has been amply demonstrated in HIV care although the evidence on what works to ensure respectful treatment by providers is sparser [42, 43]. Research on underlying causes of disrespectful treatment and on interventions that address this is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for better interpersonal quality of care may reflect that women experience brusque and disrespectful treatment by providers in resource-constrained health systems [40, 41]. The need for effective communication and more empathetic treatment has been amply demonstrated in HIV care although the evidence on what works to ensure respectful treatment by providers is sparser [42, 43]. Research on underlying causes of disrespectful treatment and on interventions that address this is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…First, because we used abridged versions of the parenting instruments, some subscales of the measurements used in this study merely contain two or three items. Although good internal consistency reliability was reported for each scale, psychometric properties, especially content and construct validities, of the abridged versions were likely to be poorer than those of the full versions, which were demonstrated to be good (42). Therefore, future studies that assess parenting processes should use the full version of the scales.…”
Section: Discussionmentioning
confidence: 99%
“…Another salient finding is that providers require comfort and confidence in speaking about sexual health with patients, to engender trust and allow the patient to share sensitive information in a trusting environment. 4,[34][35][36][37] Studies have shown that the quality of the interpersonal relationship between providers and patients, specifically communication, significantly predicts the likelihood of patients engaging in preventative healthcare. 2,7,[36][37][38][39] This reality underscores the importance of exploring and obtaining insight into the strategies used by health providers to engage patients and clients into care, a need this study aims to address.…”
Section: Discussionmentioning
confidence: 99%